The Relationship Between the Quality of the Internal Control System in Iraqi Commercial Banks and the Level of Operational Efficiency and the Achievement of Sustainable Financial Performance: An Analytical Field Study for the Period 2017–2024 - Hamad, Zahraa Taraf Sagheer (Research Parks Publishers, 2025)
The research paper examines the correlation between the quality of internal controls systems and operational efficiency of the Iraqi commercial banks between 2017-2024. The study utilizes the information of 15 large banks through which it analyzes the impact of internal control systems on the functioning of the bank through the quantitative analytical results such as correlation, and regression. The paper relies on COSO model to evaluate the quality of internal control and various financial ratios to determine the efficiency of the operation. The outcome shows strong relationship (r=0.758, p<0.01) between internal control quality and indicators of operational efficiency. Banks that have better internal control systems have a better cost to income ratio of 23 percent and returns on assets were better with a percentage of 18 percent. The results show that a better control environment, risk assessment processes and activities, and monitoring activities are the major factors that lead to the improvement of operational efficiency. The work matters in the literature of emerging market banking and makes evidence-based suggestions to stakeholders of the Iraqi banking sector.